Introduction to polar earth orbits (PEO) in the function of the satellite distress and safety systems (SDSS) - Dimov Stojce Ilcev (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper is described introduction of Polar Earth Orbits (PEO) in the function of the Satellite Distress and Safety Systems (SDSS) for all mobile applications. The results of a technical and economic study regarding the extension of the Inmarsat Geostationary Earth Orbit (GEO) satellite system to cover polar region are reviewed. In addition, also are examined the technical and practical aspects of providing an operational polar Mobile Satellite Service (MSS) for the provision of combined distress and safety communication solutions in conjunction with a commercial and defense communication systems for maritime, land and aeronautical applications. This study is considered several PEO satellite models and their probable costs for Search and Rescue (SAR) and determination MSS solutions. The practical usage of Low PEO constellation is realized by Cospas-Sarsat international project for SDSS.